غزوۂ خندق کی عسکری حکمتِ عملی اور جدید اسٹریٹیجک فکر: سیرتِ نبوی ﷺ کی روشنی میں ایک تجزیاتی مطالعہ: The Military Strategy of the Battle of the Trench and Modern Strategic Thought: An Analytical Study in the Light of the Prophetic Seerah (Al-Qamar, 2026)
The Battle of the Trench (Ghazwa al-Khandaq) represents a pivotal moment in Islamic military history, reflecting not only the resilience of the early Muslim community but also the remarkable strategic vision of the Prophet Muhammad ﷺ. Faced with a formidable coalition of enemies and severe resource limitations, the Prophet ﷺ employed a comprehensive defensive strategy that emphasized tactical innovation, coalition management, psychological resilience, and efficient resource utilization. This paper critically examines these strategic elements within the broader framework of modern military doctrines, highlighting how the Prophet’s ﷺ approach aligns with contemporary concepts such as pre-emptive planning, strategic deterrence, and adaptive warfare. Through this analysis, the study explores the relevance of Prophetic leadership and military insight in addressing present-day security challenges confronting the Muslim world. By drawing parallels between the Seerah and modern strategic thinking, this research seeks to demonstrate that the defensive planning and execution during the Battle of the Trench offer not only historical significance but also practical guidance for contemporary Muslim societies striving for security, stability, and self-reliance in an increasingly complex geopolitical landscape.
Keywords: Battle of the Trench, Military Strategy, Prophetic Leadership, Modern Strategic Thinking, Islamic Defense Doctrine